Determinan Konversi Lahan Pertanian di Provinsi Sumatera Barat: Analisis Data Panel Dengan Pendekatan Teori Land Rent - Reyhan umami putri robson; Joan Marta (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study examines the determinants of paddy field area (Luas Baku Sawah/LBS) in West Sumatra Province during 2019–2024. Agricultural land conversion has become a critical issue threatening regional food security, driven by sectoral economic growth and demographic pressure. Using panel data from 19 regencies/cities and Random Effect Model (REM) estimation selected through Chow, Hausman, and Lagrange Multiplier tests, this study analyzes the influence of agricultural GRDP, industrial GRDP, population, transportation and warehousing GRDP, and mining GRDP on LBS. The land rent theory, encompassing Ricardo's differential rent, Von Thünen's location theory, and Alonso's bid-rent model, provides the theoretical framework. Results show that agricultural GRDP, population, and transportation-warehousing GRDP positively and significantly affect LBS, while industrial GRDP has a significant negative effect, and mining GRDP shows no significant effect. Simultaneously, all variables significantly explain 44.44 percent of LBS variation. These findings imply that strengthening agricultural competitiveness and controlling industrial land expansion are essential for sustaining paddy field areas in West Sumatra.